QSAR Analysis of Substituted Benzylideneacetophenones as Lipid Peroxidation Inhibitors - Nagpal, Alka; Tiwari, Meena (Asian Journal of Chemistry, 2016)
A quantitative structure activity relationship study was performed on a series of substituted benzylideneacetophenones with inhibitory effect on lipid peroxidation using combination of various thermodynamic, electronic and steric descriptors. Several statistical regression expressions were obtained using multiple linear regression analysis. The best QSAR model was further validated by leave one out cross validation method. Electronic parameter (total energy) and thermodynamic parameter [dipole (DPL3) van der Waals' energy (E14)] were found to have significant correlationship.